Social networks as a platform for business marketing - Alturas, B. (2021)
In the last few years, social networks have been winning more and more space in the daily lives of users/consumers and therefore also in companies, and thus becoming an important element of interaction between both parties. Many events related with IT produce changes in society, and the social media produce changes which affect the IT consumer/user’s behavior and the online strategy of companies. This paper has the objective to analyze the attitudes of Portuguese users and the effects produced by the presence of the brands/companies on social networks. To this end, we applied questionnaires to users and we analyzed the relations between both parties in order to understand the changes that occur when this communication tool is used. We conclude that the factors that most influence the presence of companies on social networks are: effectiveness of advertising; purchase intention; form/duration of exposure to advertising; importance of brand/company and quality of available information.